Uludağ volfram yataklarının değerlendirilmesi - Ekinci, Yusuf Muammer (Fen Bilimleri Enstitüsü, 1993)
Mağmatik bir kütlenin mermerler içine sokulmasına bağlı olarak gelişen skarn ve sonrasında cevher taşıyıcı sıvıların etkisi sonucu çeşitli cevherleşmelerin görül düğü Uludağ'da» seli t ve wolf rami tin içerdiği volfram, gerek stratejik önemi, gerekse rezerv yönünden diğer cevherlerden farklı bir özellik göstermektedir. Etibank Genel Müdürlüğünce isletilmiş bu maden sahasının isletilmesi esnasında C196S-1985>, yapılan sondajlar galeri içinden alınan galeri numunelerinin analizinden sağlanan verilerin jeoistatistiksel yöntemler kullanılarak değerlendirilmesi ile rezerv hesabına ışık tutacak Jeolojik parametreler elde edilmiştir. Jeolojik parametrelerin elde edilmesinde, maden sahasında yapılmış 90 derecelik sondajların verileri ve galerilerden Kuzey-Güney ve Batı-Doğu doğrultularında alınmış oluk numunelerinin verileri kullanılmıştır. Cevher tenöründeki bu kısa mesafedeki değişimler ve tenor değerler indeki düşüklük nedeniyle düşey sondajlar, 56* sar metrelik zonlara ayrılarak değerlendirilmiştir. 2300 m. kodundan başlamak üzere düşey sondajların 2* ser metre kalınlık ağırlıklı ortalama volfram tenor değerlerinin değerlendirilmesi neticesinde, düşey yönde, 4 ayrı zon için düşey variogram hesaplanarak gösterilmiştir. Oluk numune analiz değerleri kullanılarak Kuzey-Güney Batı-Doğu doğrul tulu variogramlar hesaplanmış ve gösterilmiştir. Anizotropi'nin mevcut olusu bilinmesine rağmen verilerin sınırlı olması nedeni ile anlzotropi e- lipsoidlnin konumunu belirlemek mümkün olmamıştır. Gerek düşey variogramlar, gerekse Kuzey-Güney ve Batı-Dogu doğrultularından elde edilen variogramlar, eks- ponansiyel modele uymaktadır. Ayrıca volfram tenor değerlerinin, düşük tenor değerli cevherlerde olduğu gibi log-normal bir dağılıma sahip olduğu bulunmuştur. Volfram konsantre fiyatları» 1977 yıllarından itibaren düşme meyi Ünde olmasına rağmen nihai Ürünlerin fiyatlarında artış gözlenmektedir. Konsantre cevher olarak üretim yapmış olan Uludağ tesislerinin zarar etmesinde etkili olan nedenlerden bir tanesi de fiyatlardaki düşmedir.

This study performed as a thesis for MS degree com prises the evaluation of the Uludağ Wolfram Ore from the point of view of economic geology. The field of research is designated to be the 40- hec tar -wide open organization located in the mining fi eld in Uludağ, Bursa. In Uludağ, skarn is developed as a result of pene tration of a magmatic block into marble. In the wake of the development of skarn various ores are formed due to the effect of ore-carrying fluids. The wolfram pre sent in shell te and wolframite posseses a different characteristic for both its strategic importance and its reserve. During the drillings carried out in this mining fi eld which was run by Etibank between 1966 and 1985, some samples are taken out of the galleria. By applying geo- statistic methods on data obtained through the analysis of these samples, some geological parameters are attain ed. The geological parameters obtained from the present data by the employment of geostatistical methods are ev aluated in comparison with other factors which have an effect on whether the ore is economical and the results are compared to the outcome of previous studies. In the acquirement of the geological parameters, the data of the 90 degree vertical drilling performed in the field and the data of the groove samples collec ted from the galleries in North-South and West-East di rections have been utilized. The groove samples had been picked up in every 2 meters. In the study executed by MTA Institute for Etibank between 1965 and 1987, it is mentioned that the ore gra de varies within a small area- the presence of steril zones in a 10 square centimeters field. Having conside red the variations of the ore grade in such small dista nces and the low grade of the ore, the vertical drilli ngs are evaluated by dividing them into 56 meter- long vi zones. Starting the 2300 meter code. 2-meter width-wei ghted average ore grade values of the vertical drillings are assessed. Following this process, the vertical va- riogram is calculated for 4 different vertical zones. In order to prove the presence of anisotropy, the analysis values of the groove samples which has been collected from different galleries in different depths in two-meter intervals have been used. To this purpose, variograms are calculated in North-South and West-East directions, and the axial lengths of anisotropic ellipse are determined. Although the presence of anisotropy has been proved, due to the limited amount of data, it has not been possible to indicate the location of the aniso tropy ellipsoid. Both the vertical variograms and the variograms ob tained in North-South and West-East directions fit into the exponential model. Besides, the ore grade values of wolfram have log-normal distribution as other low-grade ores do, C Figure a, b and c) Since the ore grade values of wolfram in the field display a log-normal distribution, the logarithms of the ore grade values have been utilized in the variogram an alysis. While taking the logarithms of W03 grade values of the drillings, it has been assumed that the drillings which do not cut ores consist of 1 ppm ore. Thus, in the drillings the parts which do not cut the ore are ta ken into consideration as well. As it has been previously stated, the W03 grade va lues obtained from the drillings are width-weighted ave rages and they represent the W03 values of a 2 meter- long carrot. If we took the length of the carrot as 4 meters, the resulting W03 variance values would be low er. If we increased the length of the carrot, the vari ance would decrease more. That is, we would deviate from the point variance that we were supposed to find. In order to avoid this setback, the point variances are reached by the regular izat ion of the variogram parame ters obtained from 2-meter-long carrots. The regulari zed parameters are used in the kriging process. In the kriging process, 4 zones are determined to be 56 meters each, and they have been divided horizon tally into 8-meter-wide segments. Kriging estimation and standard deviation are attained in the average W03 vii 31 u Histogram Data file: »ISTH.MT 688. Statistics Mean : 3228.873 Variance: 14198220. 8S8 SU. Vev: 3768.852 ;{ Coef.tfar: 116.599 Skeamss: 2.257 Xurtosis: 18.884 PPM Figure a: Histogram for WG3 ppm Vlll Histogram »ata file: MSTB.MT - i - xi- H Total N Miss N Used Statistics NİJIİMUM 25th A Median 75th A flaxiwut LHQ403 ppO 1278 a 1278 7.347 1.836 1.355 18.441 -.333 4.605 6.386 7.496 8.466 18.342 Figure b: Histogram for LN ( W03 ppm) IX fontal Probability Plot for LNCH03 ra*) Bata file: »ISTIt.Dai Ift I© I* n ıa 38 sa 78 n Cumulative Percent 99 t a t i s t i c Figure c: Hormal Probability Plot for LN fW03 ppm, grade values of the drillings. The level plans showing the locations of drillings with different depths and 8 meter widths have been divi ded into 10x10 grids» and for each block limited by each grid, block estimation and standard deviation values ha ve been found. In the kriging process, the Ordinary Kriging method is chosen. In this process the range values gained in North-South and West-East directions are used as the ax- ises of the search ellipse. In other words, the major axis is taken into account as 54 meters in Vest-East di rection, and the minor axis as 48 meters North-South di rection During the examination of the search ellipse, for every block penetrated by at least one drilling, kriging values have been calculated. This diminishes the preci sion of the kriging values. The kriging values for most blocks couldn't be calculated as the drillings in the field were irregular and insufficient. During the project phase of the facilities which started production in 1977 and was closed due to being un- economical, it was anticipated that the facility was going to treat 5100 ppm WQ3 graded ore. In the assess ment of the reserve, the reserve of the ore with higher value than this ore grade has been taken into considei - ation. In more than 10 years when the facility was in op eration, different blocks in various dimensions were ta ken out from different depths. Now, it is not definite ho* many blocks were extracted from levels at which pro duction was carried out. The inexistence of produced blocks has not been considered in calculating the reser ve. In the calculation of reserve, volume-weighted den sity values have been utilised as density values. In previous studies in the field, six different types of occurences were determined and their volumes were cal culated separately. The density values which are of di fferent values for each occurence have been evaluated as volume-weighted and an average density value is reac hed.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1993
Keywords: Jeoloji Mühendisliği; Tungsten; Uludağ; Geological Engineering; Tungsten; Uludağ